When Employees Go to Court: Employee Lawsuits and Talent Acquisition in Audit Offices - CHEN, JADE HUAYU (Journal of Accounting Research, 2024)
ABSTRACT I examine whether employee‐initiated lawsuits against an audit office adversely affect its ability to attract high‐quality talent and deliver quality audits. I posit that employee lawsuits erode prospective employees’ perceptions of an office, diminishing their willingness to join. Using a comprehensive data set of individual auditor profiles, I find a decline in the quality of newly hired auditors following an employee lawsuit. Cross‐sectionally, the adverse effect of employee lawsuits on talent acquisition is more pronounced when an office is undergoing higher growth and when a case receives greater media attention. Conversely, this adverse effect is less pronounced when an audit office is larger or offers more competitive wages within the local area. When an audit office is unable to recruit high‐quality talent, its audit quality is likely to suffer. Consistent with this, I find a deterioration in audit quality provided by an office following an employee lawsuit. Overall, this study underscores the importance of human capital management and employer reputation for audit offices that operate in competitive labor markets.